PNEUMATIC LANDSLIDE GENERATOR - Fritz, Hermann M.; Moser, Peter (International Journal of Fluid Power, 2003)
A pneumatic landslide generator was developed specifically for the investigation of landslide generated impulse waves in reservoirs, lakes, bays or oceans in a two-dimensional physical laboratory model. The landslides were success-fully modelled with an artificial granulate. The pneumatic landslide generator was designed to control the slide impact characteristics and enable exact reproduction and independent variation of single dynamic slide parameters. The two pneumatic linear drives catapulted the landslides to velocities up to 7.3 m/s on an acceleration distance of less than 0.9 m. The operation of linear drives 3.6 times beyond their certified velocity range is highlighted. Total masses of up to 174 kg were accelerated. The slotted cylinders enabled a compact mechanical design and a stroke length equal to 70% of the overall cylinder length. The pneumatic deceleration by temporary airflow and pressure gradient reversal is pre-sented. Real time valve response problems in high-speed applications are discussed and solved with preset trigger sig-nals programmed to the pneumatics control unit. The behaviour of the whole pneumatic system was successfully simu-lated with the computer aided cylinder optimisation system software (CACOS). The measurements and numerical simu-lations are compared.